DISEASES OF THE HEART AND VASCULAR SYSTEM IN NEWBORNS - Inakova Barno Bakhadirovna (Scholar Express Journals, 2024)
The article presents the modern classification and clinical and morphological characteristics of primary and secondary cardiomyopathies in newborns and young children. The etiology and mechanisms of development of the most common cardiomyopathies are analyzed. Aspects of such rare cardiomyopathies as non-compact spongy myocardium and histiocytoid cardiomyopathy are covered. The issues of etiopathogenesis, clinical picture, pathomorphology and outcomes of posthypoxic cardiomyopathy, which occupies a leading place in the structure of causes of perinatal morbidity and mortality, are presented in detail.
Keywords: newborns; cardiomyopathy; morphology